Descriptive Analysis of Learning Difficulties on the Basic Chemistry Course - Novrita Mulya Rosa; Fatwa Patimah Nursa'adah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
Abstract. The purpose of the study is to describe (1) the difficulties experienced by students in solving basic chemistry problems, (2) factors that cause student learning difficulties in learning basic chemistry. This research is descriptive research with qualitative and quantitative approaches. Research subjects of Mathematics Education Study Program students who attend odd semester 2018/2019 basic chemistry lectures. The selection of sample classes uses purposive sampling technique. Data collection techniques were carried out by carrying out a question-based test in the form of descriptions and non-tests in the form of questionnaires and interviews. The results showed that the absorption of students for limiting reagents was 56.95%, calculation of acid base ph was 60.5%, identification of base acids 59.55%, colloids 64.1%, naming hydrocarbon compounds 64.9%, and writing structures ahaidrocarbon compounds 67.35%. Factors that cause learning difficulties consist of interest, motivation, concentration, study habits, intelligence. Student interest is 40%, motivation is 24%, concentration 36%, study habits 32%, and intelligence 28%